Situation Report: Poland, 29 May 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Polish-West German Relations Church Affairs Deputy Premier Jaroszewicz on Warsaw Comecon Session Two Economic Regulations Funeral of General Anders The Warsaw Book Fair Death of Leonid Teliga Comings and Goings